KEMAMPUAN GEOLOGI TEKNIK UNTUK PENGEMBANGAN KAWASAN WISATA DAERAH EMBUNG JURANG JERO, HARJOBINANGUN, PAKEM, SLEMAN, YOGYAKARTA - Wisnu Aji Dwi Kristanto; I Putu Gema Bujangga (KURVATEK, 2020)
Embung is an artificial building with the main function of collecting and distributing surface water. However, embung has a tourist attraction that is starting to become a trend of society. The development of the embung as a function of tourism must be supported by technical aspects, one of which is the engineering geology capability which is a measure of land suitability. Embung Jurang Jero was built in 2009 in Jurang Jero village, Harjobinangun, Pakem, Sleman, Yogyakarta with a capacity to accommodate 32,828.88 m3 of water. Located on the lower slopes of Merapi Volcano with natural attractions that support being developed into a tourist area. Thus, it is interesting to do research on the engineering geology capability of the embung Jurang Jero area for the development of environmentally friendly tourism areas. This research was conducted by mapping and weighting analysis of supporting parameters consisting of rock and soil carrying capacity, slope, geological hazard potential, groundwater depth, ease of excavation, and land use. The results showed three zones of engineering geology capability for the development of tourist areas in the form of high, medium, and low capability zones.Keywords: capability, Engineering Geology, embung, tourism, Jurang Jero.